Gut flora reflects potential risk factors for cognitive dysfunction in patients with epilepsy - BingCong Hong (BMC, 2024)
Abstract Objective This cross-sectional study aims to analyze the differences in gut flora between patients with epilepsy with and without cognitive impairment and normal subjects. Methods One hundred patients with epilepsy who came to our hospital from 2020.12 to 2022.12 (epilepsy group) were selected, and another 100 family members of the patients were selected as the control group (control group). Patients with epilepsy were further classified by the MMSE scale into 62 patients with combined cognitive impairment (Yes group) and 38 patients without cognitive impairment (No group). Detection of gut flora in feces by 16 S rRNA high-throughput sequencing. Logistic regression was used to analyze risk factors for cognitive dysfunction in patients with epilepsy. Results There were more significant differences in the structure and composition of the gut flora between patients in the epilepsy group and the control group, but no significant differences in diversity analysis (P > 0.05). Actinobacteriota, Faecalibacterium and Collinsella were significantly lower in the Yes group than in the No group (P < 0.05), and the Alpha diversity index was numerically slightly smaller than in the No group, with the PCoA analysis demonstrating a more dispersed situation in both groups. Five metabolic pathways, including glycolysis and heterolactic fermentation, were upregulated in the Yes group. LEfSe analysis showed that five groups of bacteria, including Coriobacteriaceae and Collinsella, were selected as marker species for the presence or absence of comorbid cognitive impairment. Of these, Collinsella, Oscillospirales, and Ruminococcaceae have a greater impact on epilepsy combined with cognitive impairment. Conclusion There was an imbalance in the gut flora of patients with epilepsy compared to healthy controls. The gut flora of patients with epilepsy with cognitive dysfunction differs significantly from that of patients without cognitive dysfunction. Collinsella, Oscillospirales, and Ruminococcaceae have a greater impact on epilepsy with cognitive dysfunction and can be used as an indicator for the observation of epilepsy with cognitive dysfunction.